ФОРМУВАННЯ ДОХОДІВ МІСЦЕВИХ БЮДЖЕТІВ В УМОВАХ ДЕЦЕНТРАЛІЗАЦІЇ ФІНАНСОВИХ РЕСУРСІВ - Трусова, Наталя Вікторівна; Сизоненко, Олена Василівна (Науковий журнал «Світ фінансів», 2019)
Трусова Н. В., Сизоненко О. В. Формування доходів місцевих бюджетів в умовах децентралізації фінансових ресурсів. Розглянуто теоретичні питання формування дохідної частини місцевих бюджетів. Досліджено структуру розподілу податкових і неподаткових надходжень між рівнями бюджетної системи України, визначено роль місцевих податків і зборів, а також міжбюджетних трансфертів у системі доходів бюджетів об’єднаних територіальних громад. Розглянуто вплив реформи децентралізації на формування дохідної частини місцевих бюджетів. Досліджено особливості формування місцевих бюджетів європейських країн на прикладі Польщі. Трусова Н. В., Сизоненко Е. В. Система государственного социального страхования: опыт Украины и Германии. Рассмотрено теоретические вопросы формирования доходной части местных бюджетов. Исследовано структуру распределения налоговых и неналоговых доходов между уровнями бюджетной системы Украины, роль меcтных налогов и сборов, а также межбюджетных трансфертов в системе доходов бюджетов объединенных территориальных общин. Определено влияние реформы децентрализации на формирование доходной части местных бюджетов. Рассмотрено особенности формирования местных бюджетов европейских стран на примере Польши. Trusova N., Syzonenko O. Formation of local budget revenues in the conditions of decentralization of financial resources. Introduction. Increasing the profitability of local budgets is an important issue on the way to the plundering of territorial communities, because local budgets take the main place in the socio-economic development of the territories. Particular relevance of this issue comes in terms of decentralization reform, which gives new opportunities for increasing thefinancial base of local budgets. Purpose. The purpose of the paper is to identify the peculiarities of the formation of revenues of local budgets of Ukraine in the conditions of decentralization of financial resources. Results. The theoretical questions of formation of the revenue part of local budgets are considered. The structure of the distribution of tax and non-tax revenues between the levels of the budget system of Ukraine, the role of inter-governmental transfers in the system of budget revenues of the combined terri-torial communities are investigated. The influence of decentralization reform on formation of the revenue part of local budgets is determined. Conclusions. The changes that have been made to the budget legislation in the process of decentralization reform have affected the structure of distribu-tion and source of local budgets, and strengthened the financial base of local authorities. However, it is precisely from the efforts of local self-government, the adoption of quality management decisions depends on the rational and effi-cient use of budget funds and the successful development of the community.